Autoimmune/Inflammatory Syndrome Induced by Adjuvants Causing Myositis and Pulmonary Fibrosis (2013)
Anaphylaxis is defined as a serious, rapid onset, systemic allergic reaction that may cause death.1-5 The diagnosis is based primarily on clinical history, and clinical criteria for accurate and early identification of anaphylaxis have recently been established.1 The lifetime prevalence of anaphylaxis from all triggers is estimated to range from 0.05% to 2.6%. Data on anaphylaxis Anaphylaxis online survey in Latin America Sole´ D et al.